Unravelling the effects of the food components ascorbic acid and capsaicin as a novel anti-biofilm agent against Escherichia coli - Silva, Hevelin Regiane Augusto; de Souza, Gabrielle Messias; Fernandes, José Diego [UNESP]; Constantino, Carlos José Leopoldo [UNESP]; Winkelstroter, Lizziane Kretli (Springer Nature, 2020)
This study aimed to evaluate the influence of capsaicin and ascorbic acid on the physiology of biofilm formation and dispersion. The influence of the E. coli ATCC 25922 biofilm and five E. coli isolates were observed in the presence of sodium hypochlorite 2.5 mM and subinhibitory concentrations of capsaicin (7 mM) and ascorbic acid (100 mM). The cells counts were performed through standard plaque count and the architecture visualized by confocal microscopy. The proteins, carbohydrates, and DNA present in the biofilm matrix were also quantified. There was a reduction in adhered cells in the presence of capsaicin (7 mM) and ascorbic acid (100 mM) in the biofilm formation kinetics, however, regarding the dispersion, only capsaicin altered the biofilm, data confirmed by confocal fluorescence microscopy (p < 0.05). It was noted that the matrix composition is dynamic and may be affected by changes in growth conditions such as the presence of antimicrobial substances.
Keywords: Adhesion; Carbohydrate; Confocal microscopy; DNA; Protein